Knowledge & Treatment of Students Who are Potentially Dyslexic: Teachers Perspectives - Septiani, Komang; Artini, Luh Putu; Ana, I Ketut Trika Adi (JEdu: Journal of English Education, 2025)
This study aims to: (1) explore classroom teachers knowledge of dyslexia in teaching English as a Foreign Language (EFL) to second-grade elementary school students who are potentially dyslexic; and (2) examine the classroom treatments or support provided for those students. A qualitative case study approach was employed, with data collected through semi-structured interviews and classroom observations at three public elementary schools in Singaraja, Bali. This method facilitated a comprehensive exploration of teachers knowledge of dyslexia and the treatments they provide to support students who are potentially dyslexic. The participants were classroom teachers responsible for teaching English to second-grade students. The study focused on teachers knowledge and the treatments offered to students showing signs of potential dyslexia. Among the three teachers interviewed, varying levels of understanding regarding dyslexia were evident. Only one teacher was able to relate certain student difficulties specifically in reading, writing, and spelling to dyslexia. In contrast, the other two teachers observed similar challenges but did not associate them with dyslexia. Furthermore, none of the participants demonstrated awareness of the broader range of dyslexia-related characteristics, such as difficulties in phonological processing, memory, or visual perception. As a result, the treatments provided were general in nature such as extended time, verbal encouragement, and individualized support but lacked specialized approaches, including multisensory techniques or assistive technologies. These findings suggest the need for targeted teacher training and inclusive practices to support potentially dyslexic students more effectively.